Diet, physical activity, obesity and related cancer risk: strategies to reduce cancer burden in the Americas - Mariana C Stern; Joaquin Barnoya; John P Elder; Katia Gallegos-Carrillo (Instituto Nacional de Salud Pública, 2019)
With increased globalization, Latin America is experiencing transitions from traditional lifestyle and dietary practices to those found in higher income countries. Healthy diets, physical activity and optimal body fat can prevent approximately 15% of cancers in low-income and 20% in high-income countries. We discuss links between diet, obesity, physical activity and cancer, emphasizing strategies targeting children to decrease risk of obesity, control obesity-related risk factors, and reduce sedentary lifestyles, as this will have high impact on adult cancer risk. We focus on individual behaviors, economic, cultural and societal changes that may guide future interventions in the Americas.